Energy and climate change in China - Carlo Carraro; Emanuele Massetti (Fondazione Eni Enrico Mattei (FEEM), 2011)
The paper examines future energy and emissions scenarios in China, presenting historical data and scenarios generated using the Integrated Assessment Model WITCH. A Business-as-Usual scenario is compared with four scenarios in which Greenhouse Gases emissions are taxed, at different levels. Key insights are provided to evaluate the Chinese pledge to reduce the emissions intensity of Gross Domestic Product by 40/45 percent in 2020 contained in the Copenhagen Accord. Marginal and total abatement costs are discussed using the OECD economies as a term of comparison. Cost estimates for different emissions reduction targets are used to assess the political feasibility of the 50 percent global reduction target set by the G8 and Major Economies Forum in July 2009.
Keywords: Q4; 330; Climate Change; China; Energy Efficiency; Energy and Development; Klimaveränderung; Kohlendioxid; Klimaschutz; Energieeffizienz; Szenariotechnik; China